Sensorial comparison of fine aroma cocoa type Nacional (Theobroma cacao L.) grown in different zones of Ecuador - Solórzano Chavez, Eddyn (2015)
The present study aimed at comparing the flavor profiles in bean samples from different cocoa growing zones of Ecuador. Samples were taken from commercial cocoa bean batches at the post harvest facilities of 11 cocoa grower associations. They sent the samples to the Chocolate and Cocoa Integral Quality Laboratory of Experimental Station Tropical Pichilingue-INIAP. Cocoa paste (liquor) obtained for each sample was tested by a five member panel to produce scores for the sensorial variables: cocoa, acidity, bitterness, astringency, sweetness, floral, frutty, nutty and raw. Kruskal-Wallis nonparametric test was applied to compare the samples. Correlation coefficients were calculated to explore the degree of closeness between different pairs of variables. Sample relationships were also examined through principal component multivariate analysis, which led to the identification of the original variables with the highest contribution to the variance in the two first principal components. Statistical differences among samples were found for cocoa flavour only. High correlation coefficients, most of negative sign, were found for frutty and raw, frutty and astringency, frutty and bitterness, and frutty and nutty. The highest contribution (35.20%) to first principal component variance were made by: frutty, raw and bitterness. Those contributing most to the second component´s total variance were: acidity, floral and nutty. The apparent structuring of two sample groups on the plane defined by the two main principal components suggests the existence of similarities and differences in their sensorial profiles.